2007
DOI: 10.1017/s0029665107005460
|View full text |Cite
|
Sign up to set email alerts
|

Life-course approaches to inequalities in adult chronic disease risk

Abstract: A life-course approach to chronic-disease epidemiology uses a multidisciplinary framework to understand the importance of time and timing in associations between exposures and outcomes at the individual and population levels. Such an approach to chronic diseases is enriched by specification of the particular manner in which timing in relation to physical growth, reproduction, infection, social mobility, behavioural transitions etc. can influence various adult chronic diseases in different ways, and more ambiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 120 publications
(194 reference statements)
1
40
0
Order By: Relevance
“…Optimism has been shown to mediate the association between parental education and perceived stress among teens 28. Several studies have shown the life-long accumulation of CVD risk with socioeconomic disadvantage 2931…”
Section: Discussionmentioning
confidence: 99%
“…Optimism has been shown to mediate the association between parental education and perceived stress among teens 28. Several studies have shown the life-long accumulation of CVD risk with socioeconomic disadvantage 2931…”
Section: Discussionmentioning
confidence: 99%
“…74 As the cumulative life course effect of adverse SEP on adult disease outcomes become more apparent, the need to adjust for different measures of SEP from across the life course in observational studies of exposures and outcomes that are strongly socially patterned is increasingly acknowledged. 75 It is unlikely that residual socioeconomic confounding can be ruled out by simple adjustment for one or perhaps two measures of SEP at a single point in time. 76 …”
Section: Area Level Measures (Indices Of Deprivation)mentioning
confidence: 99%
“…Various studies have investigated the effects of individual socioeconomic trajectories over time on cardiovascular diseases (Davey Smith, Ben-Shlomo, & Lynch, 2002;Lamont, Parker, White, Unwin, Bennett, Cohen et al, 2000). However, to our knowledge only few studies have focused on the socioeconomic transition from active life to retirement (Wolfson, Rowe, Gentleman, & Tomiak, 1993).…”
Section: Introductionmentioning
confidence: 99%